2021
DOI: 10.1007/s40264-021-01085-9
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review of Non-Medical and Extra-Medical Use of Non-Steroidal Anti-Inflammatory Drugs (NSAIDs)

Abstract: Non-steroidal anti-inflammatory drugs (NSAIDs) are among the most commonly used medications worldwide and have analgesic, antipyretic and anti-inflammatory properties. Although NSAIDs are recognised as generally safe and effective, non-medical and extra-medical use of these products can occur. Unlike the use of illegal and many prescription drugs, which are subject to extensive research attention, inappropriate use of NSAIDs has been less well investigated. This scoping review collates and describes what is kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 79 publications
1
21
0
1
Order By: Relevance
“…For instance, in these countries, OTC analgesics can be purchased in local supermarkets or at gas stations which might create the impression to the public that these drugs are safer than prescription-only drugs, potentially resulting in higher rates of frequent and problematic use ( 49 ). Finally, the use of inconsistent definitions of abuse and misuse leads to different results in the estimation of NOA abuse between studies ( 19 , 50 ). The development of standardized substance abuse terminology is urgently needed to compare prevalence estimates between countries ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in these countries, OTC analgesics can be purchased in local supermarkets or at gas stations which might create the impression to the public that these drugs are safer than prescription-only drugs, potentially resulting in higher rates of frequent and problematic use ( 49 ). Finally, the use of inconsistent definitions of abuse and misuse leads to different results in the estimation of NOA abuse between studies ( 19 , 50 ). The development of standardized substance abuse terminology is urgently needed to compare prevalence estimates between countries ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…The top five causes of hospital admissions include serious complications related to the use of these drugs [ 25 ]. This is especially true for over-the-counter drugs from the group of Non-steroidal anti-inflammatory drugs (NSAIDs) [ 13 ], which are responsible for approximately 25% of all drug-related complications [ 10 , 26 , 27 , 28 ].…”
Section: Health Risks Associated With the Use Of Otc Medicinesmentioning
confidence: 99%
“…We hypothesize that this is because NSAIDs are the most commonly prescribed drug group in Turkey and worldwide. 16 Analysis of the NSAID groups revealed that propionic acid derivatives were the most commonly used (n = 42), followed by acetic acid derivatives (n = 11), acetyl salicylic acid (n = 10), and phenyramidol (n = 8). Acute urticaria was also noted in 13 patients after paracetamol use.…”
Section: Strong Pointsmentioning
confidence: 99%